From Doctrine to Domestic Resilience: The Lived Meaning of Mīṡāqan Ghalīẓan among Salafi Families - Tri Wahyu Hidayati; Siti Robikah; Muhyar Fanani; Ahmad Baha (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2026)
This article examines the lived meaning of mīṡāqan ghalīẓan, the solemn marital covenant articulated in Q.S. al-Nisāʾ [4]:21, among Salafi families in Semarang Regency, Indonesia. Focusing on how these families respond to domestic tensions and economic pressures, the study situates mīṡāqan ghalīẓan at the intersection of Qur’anic exegesis, maqāṣid al-sharīʿah, and everyday marital practice. Based on qualitative fieldwork involving in-depth interviews and participant observation, the article shows that mīṡāqan ghalīẓan is not understood merely as a juridical formula within marriage, but as a moral-spiritual covenant that shapes spousal relations, conflict resolution, and household economic decision-making. The findings reveal that marital disagreements are commonly managed through musyāwarah, ethical self-restraint, and mutual accountability, while economic hardship is interpreted as a spiritual trial requiring patience, cooperation, and shared responsibility. These practices challenge the common assumption that Salafi marital life is inherently rigid, patriarchal, or authoritarian. Instead, they reveal a relational ethic rooted in religious discipline, negotiated responsibility, and moral accountability. Seen from the maqāṣid al-sharīʿah, these practices help protect five essential values in Islam: religion, life, intellect, family lineage, and property. By connecting Qur’anic interpretation with lived marital experience, this study contributes to contemporary debates on Islamic family ethics, Salafi social practice, and Muslim family resilience. It argues that mīṡāqan ghalīẓan operates not only as a theological and legal concept, but also as a dynamic ethical framework for sustaining family resilience in contemporary Muslim societies.